The Venom Proteome of the Ecologically Divergent Australian Elapid, Southern Death Adder Acanthophis antarcticus - Theo Tasoulis; C. Ruth Wang; Shaun Ellis; Tara L. Pukala; Joanna Sumner; Kate Murphy; Nathan Dunstan; Geoffrey K. Isbister (Toxins, 2025)
The composition of Australian snake venoms is the least well-known of any continent. We characterised the venom proteome of the southern death adder Acanthophis antarcticus—one of the world’s most morphologically and ecologically divergent elapids. Using a combined bottom-up proteomic and venom gland transcriptomic approach employing reverse-phase chromatographic and gel electrophoretic fractionation strategies in the bottom-up proteomic workflow, we characterised 92.8% of the venom, comprising twelve different toxin identification hits belonging to seven toxin families. The most abundant protein family was three-finger toxins (3FTxs; 59.8% whole venom), consisting mostly of one long-chain neurotoxin, alpha-elapitoxin-Aa2b making up 59% of the venom and two proteoforms of another long-chain neurotoxin. Phospholipase A2s (PLA2s) were the second most abundant, with four different toxins making up 22.5% of the venom. One toxin was similar to two previous non-neurotoxic PLA2s, making up 16% of the venom. The remaining protein families present were CTL (3.6%), NGF (2.5%), CRiSP (1.8%), LAAO (1.4%), and AChE (0.8%). A. antarcticus is the first Australian elapid characterised that has a 3FTx dominant venom, a composition typical of elapids on other continents, particularly cobras Naja sp. The fact that A. antarcticus has a venom composition similar to cobra venom while having a viper-like ecology illustrates that similar venom expressions can evolve independently of ecology. The predominance of post-synaptic neurotoxins (3FTxs) and pre-synaptic neurotoxins (PLA2) is consistent with the neurotoxic clinical effects of envenomation in humans.